2016
DOI: 10.1536/ihj.15-505
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Combination of Interatrial Block and a High CHADS<sub>2</sub> Score to Predict New Onset Atrial Fibrillation

Abstract: SummaryInteratrial block (IAB) is associated with an increased risk of atrial fibrillation (AF). The aim of this retrospective study was to investigate the association of a combination of IAB and the CHADS 2 score, an AF-related risk score for ischemic stroke, with new onset AF in patients in sinus rhythm. A total of 1,571 patients (803 males, 768 females; mean age: 58 ± 16 years) were included in this study. IAB was defined as a P-wave duration > 120 ms in the 12-lead electrocardiogram, and a high CHADS 2 sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Second, Pwave duration was measured manually and not with semiautomatic calipers, 33,34) which is considered a more sophisticated way to determine P-wave duration. Third, because a higher CHADS2 score is associated with a higher risk of AF, 3,18) more patients with a higher CHADS2 score may have had AF at baseline. Thus, some patients with high CHADS2 scores were excluded from the study population because patients with known AF were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Pwave duration was measured manually and not with semiautomatic calipers, 33,34) which is considered a more sophisticated way to determine P-wave duration. Third, because a higher CHADS2 score is associated with a higher risk of AF, 3,18) more patients with a higher CHADS2 score may have had AF at baseline. Thus, some patients with high CHADS2 scores were excluded from the study population because patients with known AF were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
“…1) A recent review of the prevalence of IAB described this condition as being an under-appreciated clinical pandemic, particularly in the aging population. 2) IAB can be associated with a multitude of medical conditions, including atrial fibrillation (AF), [3][4][5][6][7][8] left atrial electromechanical dysfunction, 1,9) thromboembolic ischemic stroke, [10][11][12][13] and increased cardiovascular and all-cause mortalities. 14) Therefore, it is crucial that patients who are at an increased risk for developing IAB are identified.…”
mentioning
confidence: 99%
“…Ariyarajah et al . found a higher IAB prevalence in patients with previous embolic stroke than in patients with a nonembolic stroke (61% vs 41%; P < 0.05) and some other studies also support the same relation between the presence of advanced IAB and the development of AF and ischemic stroke …”
Section: Discussionmentioning
confidence: 77%
“…A systematic review and meta‐analysis has shown that IAB is a significant predictor of new onset AF, with hazard ratio (HR) of 2.42, and of AF recurrence after ablation (HR: 2.59; Tse et al, ). Wu et al showed that IAB in SR and CHADS 2 score independently and synergistically predicted new‐onset AF (Wu et al, ). A positive predictive accuracy of 79% in separating patients with PAF from control subjects has been reported with ECG measurement of PWD using a P maximum value of 106 ms (Pérez‐Riera et al, ).…”
Section: Discussionmentioning
confidence: 97%